ANALISIS KINERJA KEUANGAN PADA PT. ASTRA INTERNATIONAL, TBK - S.F. Supit, Thessalonica; A. Areros, Welly .; .R.E. Tampi, Johny (Sam Ratulangi University, 2016)
Abstract. This study aimed to analyze the financial performance of PT. Astra International Tbk based Ratios Liquidity, Solvency and Profitability